Chapter San Miniato e le origini del monachesimo vallombrosano - Salvestrini, Francesco (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2021)
The paper dwells on Giovanni Gualberto's relations with San Miniato al Monte and the Apostolic See, and questions some consolidated historiographical paradigms to highlight the elements of continuity the new 'Vallombrosan' foundations held with the Benedictine monastic tradition. The thesis is that the very hard opposition to Abbot Ubertus did not lead to a break with the Abbey of the Mons Forentinus. The reinterpretation of the Florentine reforming movement shows how Giovanni Gualberto's rebellion was linked to practical and disciplinary rather than doctrinal aspects, and how the subversive thrust of his positions, both in terms of Eucharistic theology and the validity of the sacraments administered by unworthy priests, was emphasised by the deforming point of view of the controversies of the time, mainly in the vision of Peter Damiani.